Tilapia skin peptides restore cyclophosphamide-induced premature ovarian failure via inhibiting oxidative stress and apoptosis in mice. Issue 3 (27th January 2022) - Zhao, Yun-Tao; Yin, Haowen; Hu, Chuanyin; Zeng, Jian; Shi, Xinyi; Chen, Shaohong; Zhang, Kun; Zheng, Wenjing; Wu, Wenjin; Liu, Shucheng
Abstract : This study aimed to investigate the effects of Tilapia skin peptides on cyclophosphamide-induced premature ovarian failure in mice and to further elucidate the potential mechanisms. Abstract : Tilapia ( Oreochromis mossambicus ) skin high value-added compounds have not been fully utilized in tilapia processing. Here, the protective effects of tilapia skin peptides (TSP) on primary ovarian failure (POF) and their underlying mechanisms in mice were investigated. Cyclophosphamide (CP) was injected intraperitoneally (ip) for 14 days (10 mg kg −1 d −1 ) to establish a mouse model of POF. At the same time, the mice were given intragastrically (ig) TSP for 30 days (250 mg kg −1 d −1, 500 mg kg −1 d −1, and 1000 mg kg −1 d −1, respectively). The ovarian index, estrous cycle, hormone level, changes in the number of follicles at various levels, and biochemical tests were carried out at the end of the experiment. The body weight and ovarian index of mice in the POF group were markedly lower than that of the control group. Treatment with TSP reversed these changes significantly. TSP administration significantly restored the estrous cycle disorder of the mice versus that of the POF group. The level changes of progesterone (P), estradiol (E2), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) induced by CP were significantly reversed by TSP treatment. TSP inhibited oxidative stress in CP-induced mice by enhancing the total superoxide dismutase (T-SOD) activity and reducing malondialdehyde (MDA) levels in the ovaries. TSP improved the apoptosis of ovarian granulosa cells in CP-induced mice compared with the POF group. Furthermore, TSP regulated the Bcl-2/Bax/caspase-3 apoptosis pathway and enhanced the Nrf2/HO-1 signaling pathway. In conclusion, TSP could improve CP-induced POF via alleviating ovarian oxidative stress and granulosa cell apoptosis.